Prevalence of Impacted Wisdom Teeth among Hawler Young People (Mustansiria Dental Journal, 2018)
Background: It is believed that the incidence of impaction is increasing in recent years due to the less functional activity of the Jaws.Aim of the study: The objective of this study is to know the prevalence of impacted wisdom teeth among Hawler young population Also to know the factors that are associated with the state of impaction.Material and Method: 1150 young people from college of dentistry were included from February to September 2005, age ranged between 17 -30 years old they were examined using special case sheet.Results: Out of 1150 people examined (517male .and 633female), (219 male and 285 female) were found to have one or more impacted wisdom teeth (43.82%).Only 73(32male and 41 female) had one or more congenitally missing third molar. A relation was found between impaction and habit of using chewing gum and singing, statistical relation were existed between impaction and type of food, tempromandibular joint (TMJ) trouble, emotional stress and fatigue.Conclusion: A strong association was found between impacted wisdom teeth and type of food and habits among Hawler young population.